Technology Transfer of Rural Entrepreneurship Digitization to Regional Economic Growth - Prasetyo, P Eko (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: The digital technology transfer in rural entrepreneurship is a knowledge-based solidarity socio-economic (SSE) innovation that drives regional economic growth and reduces inequality.Research Objectives: This study aims to analyze the role of digitalization technology transfer in entrepreneurship on regional economic growth, inequality mitigation, and other related resource factors.Research Methods: The study approach model used a mixed methods design through exploratory and explanatory stages. The data were analyzed quantitatively descriptively with the standard multiple regression tool. The operational variables were measured using the Gini ratio index.Empirical Results: The results showed that digitalization technology transfer encourages regional economic growth. However, the positive role created has not reduced the negative impact and inequality. This inequality could be mitigated by the innovation of the community's social solidarity economic system (SSE). There are indications of the potential of local community wisdom to strengthen informal institutions in society.Implications: Utilizing the community's potential and the SSE model could provide added value for the community's welfare.JEL Classification: O14, O47, P25